The Jewish community of Rome : from the second century B.C. to the third century C.E. - Cappelletti, Silvia. (Supplements to the Journal for the Study of Judaism, 2006)
This volume deals with the development of the Jewish community of Rome in the late Republican and Imperial periods. It uses both literary and archaeological evidence, but attaches a great importance to the epigraphic source. The first section studies the structure of the community, in comparison with patterns attested both in Diaspora and in Eretz-Israel. The second section examines the historical development of the Jewish presence in Rome, and the third section deals with the structure of the catacombs and studies some interpretative problems presented by inscriptions. Through this material the book tries to find the links between this community and Mediterranean Judaism.